International Observational Analysis of Evolution and Outcomes of Chronic Stable Angina: The Multinational CLARIFY Study. Issue 7 (17th August 2021) - Mesnier, Jules; Ducrocq, Gregory; Danchin, Nicolas; Ferrari, Roberto; Ford, Ian; Tardif, Jean-Claude; Tendera, Michal; Fox, Kim M.; Steg, Philippe Gabriel
Abstract : Background: Although angina is common in patients with stable coronary artery disease, limited data are available on its prevalence, natural evolution, and outcomes in the era of effective cardiovascular drugs and widespread use of coronary revascularization. Methods: Using data from 32 691 patients with stable coronary artery disease from the prospective observational CLARIFY registry (Prospective Observational Longitudinal Registry of Patients with Stable Coronary Artery Disease), anginal status was mapped each year in patients without new coronary revascularization or new myocardial infarction. The use of medical interventions in the year preceding angina resolution was explored. The effect of 1-year changes in angina status on 5-year outcomes was analyzed using multivariable analysis. Results: Among 7212 (22.1%) patients who reported angina at baseline, angina disappeared (without coronary revascularization) in 39.6% at 1 year, with further annual decreases. In patients without angina at baseline, 2.0% to 4.8% developed angina each year. During 5-year follow-up, angina was controlled in 7773 patients, in whom resolution of angina was obtained with increased use of antianginal treatment in 11.1%, with coronary revascularization in 4.5%, and without any changes in medication or revascularization in 84.4%. Compared to patients without angina at baseline and 1 year, persistence of angina and occurrence of angina at 1 year with conservative management were each independently associated with higher rates of cardiovascular death or myocardial infarction (adjusted hazard ratio, 1.32 [95% CI, 1.12−1.55] for persistence of angina; adjusted hazard ratio, 1.37 [95% CI, 1.11−1.70] for occurrence of angina) at 5 years. Patients whose angina had resolved at 1 year with conservative management were not at higher risk of cardiovascular death or myocardial infarction than those who never experienced angina (adjusted hazard ratio, 0.97 [95% CI, 0.82−1.15]). Conclusions: Angina affects almost one-quarter of patients with stable coronary artery disease but resolves without events or coronary revascularization in most patients. Resolution of angina within 1 year with conservative management predicted outcomes similar to lack of angina, whereas persistence or occurrence was associated with worse outcomes. Because most patients with angina are likely to experience resolution of symptoms, and because there is no demonstrated outcome benefit to routine revascularization, this study emphasizes the value of conservative management of stable coronary artery disease. Registration: URL: https://www.isrctn.com ; Unique identifier: ISRCTN43070564. Abstract : Supplemental Digital Content is available in the text.